2009
DOI: 10.1037/h0100241
|View full text |Cite
|
Sign up to set email alerts
|

Parent-child interaction therapy and language facilitation: The role of parent-training on language development.

Abstract: The high rate of comorbidity between language delays and externalizing behavior problems has been well established. The enduring nature and negative projections of delayed language supports the need for further examination of language facilitation and early interventions aimed at altering language development, which may also positively influence later behavioral outcomes. Specifically, the role of parenting styles in altering both language development and behavior problems has been examined. Although independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 75 publications
0
25
0
Order By: Relevance
“…If left untreated, behavior problems may exacerbate language difficulties (Rutter & Lord, 1987), which also can impede speech and gains from speech therapy (Baker & Cantwell, 1987). Alternatively, language difficulties may have a negative impact on behavior, resulting in increased rates of inattentiveness, aggression, or social withdrawal (Tempel, Wagner, and McNeil, 2008). Given the proposed bidirectional relation between behavior problems and language difficulties, it is important to consider shared etiological influences as a potential target for intervention, such as parent-child interactions (Hart & Risley, 1995).…”
Section: Behavior Problems and Language Difficultiesmentioning
confidence: 99%
See 1 more Smart Citation
“…If left untreated, behavior problems may exacerbate language difficulties (Rutter & Lord, 1987), which also can impede speech and gains from speech therapy (Baker & Cantwell, 1987). Alternatively, language difficulties may have a negative impact on behavior, resulting in increased rates of inattentiveness, aggression, or social withdrawal (Tempel, Wagner, and McNeil, 2008). Given the proposed bidirectional relation between behavior problems and language difficulties, it is important to consider shared etiological influences as a potential target for intervention, such as parent-child interactions (Hart & Risley, 1995).…”
Section: Behavior Problems and Language Difficultiesmentioning
confidence: 99%
“…Core components of PCIT (e.g., PRIDE skills) are similar to “parallel talk” procedures that are used in speech-language interventions, suggesting PCIT may also lead to improvements in language in addition to already established decreases in child disruptive behavior. In a conceptual paper, Tempel, Wagner, and McNeil (2008) reviewed the PCIT and language development literatures to demonstrate how parents receiving PCIT can learn the necessary skills to help decrease child disruptive behaviors and simultaneously foster child language production. However, no empirical research to date has examined the effect of PCIT on child language production.…”
Section: Parent-child Interaction Therapymentioning
confidence: 99%
“…These results include: positive clinical outcomes for structured interventions that involved parents as partners in their child's speech and language therapy when the clinician remained the primary agent of intervention (Bowen and Cupples , Tempel et al . ); potential parental frustration and negative impacts on familial relationships with siblings (Shelton et al . , Watts Pappas et al .…”
Section: Introductionmentioning
confidence: 99%
“…Its emphasis is on improving the quality of the parent-child relationship, and modifying a range of behavioral, emotional, and family difficulties (Eyberg, Funderburk, Hembree-Kigin, McNeil, Querido, & Hood, 2001;Eyberg, Nelson, & Boggs, 2008;Tempel, Wagner, & McNeil, 2008). Treatment outcomes in research have demonstrated significant reduction in noncompliance/ behavioral problems (Nixon, Sweeny, Erickson, & Touyz, 2003;Schuhmann, Foote, Eyberg, Boggs, & Algina, 1998), generalization to home and school (Funderburk, Eyberg, Newcomb, McNeil, Hembree-Kigin, & Capage, 1998), maintenance of gains up to six years after treatment (Hood, & Eyberg, 2003), generalization to untreated siblings (Brestan, Eyberg, Boggs, & Algina, 1997), and changes in parents' interactional styles (Eisenstadt, Eyberg, McNeil, Newcomb & Funderburk, 1993).…”
Section: Adhdmentioning
confidence: 99%
“…PCIT balances out two factors: 1) positive interactions with the child by increasing positive attention and decreasing negative attention, and 2) Setting consistent limits which focuses on consistency, predictability and follow through (Tempel, Wagner, & McNeil, 2008). The training program consists of two phases: a Child-Directed Interaction (CDI) and a Parent-Directed Interaction (PDI).…”
Section: Adhdmentioning
confidence: 99%